Chemical Characterization of Five Tunisian Eucalyptus Essential Oils Species. Issue 1 (17th December 2019) - Elaissi, Ameur; Moumni, Sarra; Roeleveld, Kevin; Larbi Khouja, Mohamed
Abstract: Hydrodistillation of the dried leaves of five Eucalyptus species, E. alba Reinw. ex Blume, E. citriodora Hook ., E. paniculata Sm., harvested from Choucha arboreta (region of Sejnane, northwest of Tunisia), E. pimpiniana Maiden from Mjez Elbab arboreta (north east of Tunisia) and E. bicolor A.Cunn ex Hook from Sidi Smail arboreta (center of Tunisia), in March 2017, afforded essential oils in yields varying from 1.3±0.2 to 6.0±0.9 % according to the species. E. citriodora provided the highest mean percentage of essential oil amongst all the species. Analysis by GC (RI) and GC/MS allowed the identification of 138 components representing 84.6–98.7 % of the total oil. The content of the different samples varied according to the species. The main components were citronellol, followed by 1, 8‐cineole, α ‐pinene, τ ‐cadinol, 7‐ epi‐α ‐eudesmol, trans ‐pinocarveol, spathulenol, aromadendrene, γ ‐cadinene and δ ‐cadinene. The principal components and the hierarchical cluster analyses separated the five leaf essential oils into three groups, each group constituted a chemotype. Abstract :